TOURIST DESTINATION STRENGHTS AND OPPORTUNITIES: IS MONTENEGRO READY FOR CHINESE TOURISTS? - Stranjančević, Ana; Bulatović, Iva; Lacmanović, Darko; Raspor, Andrej (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2016)
Since Chinese outbound tourism currently represents the largest outbound tourist market, the opportunities for tourism of Montenegro in the Chinese tourist market should be certainly examined. The aim of this paper is to analyze the relevant data about Chinese tourists who are visiting Montenegro: their specific demographic characteristics, travel habits and main motivation, but also to identify the possible ways to increase the number of Chinese tourists in Montenegro in future. For the purpose of this paper, two years long empirical research was conducted among Chinese tourists in Montenegro with the help of questionnaire. Several interviews with representatives of tourism sector in Montenegro were carried out as well. The authors have concluded that only after the total adjustment of Montenegro tourist oﬀer to the Chinese tourists’ preferences, Montenegro could be completely ready for intensive acceptance of Chinese tourists. What’s more, in order to attract larger number of Chinese tourists, the effective marketing policy of Montenegro as a tourist destination should be created in that direction and as well the specialized tourism promotion at the Chinese market should be carried out.